Bobbin and conventional friction stir welding of thick extruded AA6005-T6 profiles. (15th October 2016) - Esmaily, M.; Mortazavi, N.; Osikowicz, W.; Hindsefelt, H.; Svensson, J.E.; Halvarsson, M.; Martin, J.; Johansson, L.G.
Abstract: Conventional and bobbin friction stir welding processes (FSW and BFSW, respectively) were employed for joining 10 mm thick extruded AA6005-T6 profiles. The FSW and BFSW techniques were employed using two sets of parameters resulting in slow and fast processes. In general, the bobbin tool enabled welding with faster welding speeds than the conventional FSW technique. A comprehensive in-situ thermal analysis was performed using thermocouples. It was evident that, in a like-for-like comparison, i.e., employing the same set of welding parameters, the BFSW technique introduces a somewhat higher peak temperature, however, lower heat input and, more importantly, a higher cooling rate than the conventional FSW. Accordingly, a somewhat finer microstructure was formed in the stir zone of the BFSW samples than in the FSW ones, resulting in higher hardness values, and slightly higher ultimate strengths in the BFSW samples. Graphical abstract: Highlights: A comparative study was conducted between FSW and BFSW (the bobbin tool). Welding by bobbin tool resulted in a faster cooling compared to conventional FSW. A finer grain structure and moderately better properties were achieved in BFSW specimens. Large variations in the grain size were observed in the stir zone of the BFSW weldments.